Low Prior Exposure and Incidence of Hepatitis C in Human Immunodeficiency Virus–Negative Gay and Bisexual Men Taking Preexposure Prophylaxis (PrEP): Findings From the Expanded PrEP Implementation in Communities–New South Wales Prospective Implementation Study . (30th March 2022) - Amin, Janaki; Vaccher, Stefanie; Templeton, David J; Bavinton, Benjamin; Jin, Fengyi; Zablotska, Iryna; Matthews, Gail; Ogilvie, Erin; Yeung, Barbara; Ooi, Catriona; Dharan, Nila; Baker, David A; et al.
Abstract: Background: The use of preexposure prophylaxis (PrEP) for the prevention of human immunodeficiency virus (HIV) has raised concerns of increased sexual risk behaviors. These behaviors may be associated with increased incidence of sexually acquired hepatitis C virus (HCV) among gay and bisexual men. Methods: The Expanded PrEP Implementation in Communities–New South Wales (EPIC-NSW) study was a cohort study of daily coformulated tenofovir disoproxil fumarate and emtricitabine for HIV prevention. We recruited 9596 people at high risk of HIV acquisition from 31 clinics across New South Wales and the Australia Capital Territory in Australia. We report prior exposure to HCV and incidence in this cohort between 2016 and 2019. Results: At least 1 HCV test result was available for 8658 (90.2%) participants. These individuals had a median age of 34 years (interquartile range, 28–43), most of whom were male (8530, 98.5%), identified as gay (7944, 91.8%), and were born in Australia (51.8%). Prior exposure to HCV was detected among 81 participants at baseline (0.9%; 95% confidence interval [CI]: .71.2). Twenty of 8577 participants were diagnosed with incident infection (rate 0.2/100 person-years [95% CI: .1–.3/100 person-years]). They were significantly older (median age 41 years vs 34 years, P = .044), and more likely to report methamphetamine use at baseline (incidence rate ratio, 2.7 [95% CI: 1.00–7.2]) than those without incident infection. Conclusions: In this population of PrEP users, HCV prior exposure and incidence were low. With high levels of HCV and HIV testing and treatment, the dual goals of HIV and HCV elimination could be achieved in this population. Clinical Trials Registration: number NCT02870790. Abstract : In this population-based study of more than 8000 gay and bisexual men at high risk for human immunodeficiency virus infection on preexposure prophylaxis, we report very low prevalence of prior and on-study incidence of hepatitis C virus.